Weedy rice: an emerging threat - Rathore, Meenal; Singh, P. K.; Abraham, C T; Jose, Nimmy (Indian Farming, 2018)
The menace of weedy rice (Oryza sativa f. spontanea) has risen globally during the last decade. Being a natural introgression between wild and cultivated rice, weedy rice bears intermediary characters and a weedy nature. The important, distinguishing and undesirable traits of weedy rice include easy shattering of seeds, variable seed dormancy, high seed persistence in soil and high nitrogen use efficiency. Hull induced dormancy and high soil persistence favour staggered germination of weedy rice in infested cropped field. Being a biochemical mimicry weed, no selective herbicide is available to manage weedy rice. Preventive measures like use of clean/ certified seeds, clean machinery and irrigation water; cultural methods like stale seed bed technique, crop rotation, repeated tillage etc. can help manage it and reduce the weed seed bank. An indispensable measure is the need to create awareness about weedy rice among farmers and our scientific fraternity.